Key audit matters and their implications for the audit environment. (28th September 2020) - Botes, Vida; Low, Mary; Sutton, Aleena
This paper sets out to investigate how the new auditing standard ISA 701: key audit matters addresses issues historically presented by audit reports. The extensive literature around audit reporting highlights that past reforms resulted in a lack of success and the continued existence of the audit expectation gap. Increased auditor liability is one of the major concerns raised by practitioners with the new standard expanding the audit report to include key audit matters. Through a qualitative content analysis examination of the most recent audit reports of the top 100 listed companies on the NZX, ASX and FTSE, key audit matters were identified. The results of the study found that goodwill and intangibles, revenue recognition and taxation were the most common key audit matters. Overall, the results of these findings suggest that these key audit matters may go a long way to addressing the audit expectation gap and issues presented by audit reports.